Exploring the Determinants of Citizens’ Compliance with COVID-19 Regulations: Legitimacy Versus Fear - Gurinskaya, Anna (Criminal justice review, 2024)
This paper explores factors shaping citizens’ obligation to comply with COVID-19 prevention strategies, such as mandatory mask-wearing and recommended social distancing, contact limitation, and stay-at-home measures. The central focus is to assess the relationship between dimensions of state authorities’ legitimacy (normative alignment, obligation to obey, and support for COVID-19 mitigation mandates) and fear factors (risk of sanctions and infection) on citizens’ willingness to comply with COVID-19 mandates. Data for the study came from 508 respondents from Russia's second-largest city, St. Petersburg—in May 2020, when the COVID-19 regional legislation that mandated citizens to wear masks in public went into effect. Overall, our findings suggest that normative alignment and obligation to obey do not directly influence compliance but have an impact through support for regulations. Additionally, fear factors of perceived police sanctions, COVID-19 infection, and self-morality were positively related to compliance.